Damping Capacity in Fe-27Mn-3.5Si Alloy - Jee, K.K.; Shin, M.C.; Ito, K. (1994)
Damping capacity in an Fe-27Mn-3.5Si alloy has been greatly improved with significant anisotropy by cold-rolling. The alloy, consisting of stacking faults and thermal ε martensite before rolling, shows poor damping capacity at low strain amplitude and strong amplitude dependence. The increase and anisotropy in the damping capacity are attributed to ε martensite induced by cold-rolling. The alloy is found to adjust itself to the deformation by forming ε martensite which has a preferred orientation of [formula omitted]. The mechanism of formation of the preferred orientation can be explained by the shear model in γ→ε transformation. With the result of microstructure and preferred orientation, a damping mechanism by ε martensite and its anisotropy is discussed. ？ 1994, The Iron and Steel Institute of Japan. All rights reserved.
Keywords: Anisotropy; Cold rolling; Crystal microstructure; Crystal orientation; Damping; Deformation; Martensite; Mathematical models; Phase transitions; Specimen preparation; Stacking faults; Strain; Damping capacity; Iron manganese silicon alloy; Preferred orientation; Iron alloys